Tax collection, the informal sector, and productivity - Julio C. Leal-Ordo\~nez (Banco de México, 2013)
Some authors argue that informality is associated with distorted firm decisions and inefficiency. In this paper, I assess the quantitative effect of incomplete tax enforcement on aggregate output and productivity using a dynamic general equilibrium framework. I calibrate the model using data for Mexico and investigate the effects of introducing enforcement improvements. Under complete enforcement, labor productivity and output would be 19% higher under perfect competition and 34% higher under monopolistic competition. The source of this gain is the removal of distortions induced by incomplete enforcement of taxes which affect the economy in three ways: by reducing the capital-labor ratios of informal establishments; by allowing low-productive entrepreneurs to enter; and by misallocating resources towards low-productive establishments. I isolate the effects of pure factor misallocation, distorted occupational choices, capital accumulation, and complementarities.
Keywords: E23; E26; O17; O40; 330; tax enforcement; TFP; the informal sector